Peran Komite Sekolah dalam Mengembangkan Mutu Sekolah - Maulia, Mia; Sti Zafira Qia; Aliyyah, Rusi Rusmiati (Indo-MathEdu Intellectuals Journal, 2026)
The School Committee is an independent institution that plays an important role in improving the quality of education through community involvement. This study aims to analyze the role of the School Committee based on four main functions, namely as an advisory body, supporter, controller, and mediator. This research employs a qualitative method with a literature review approach. Data sources were obtained from books, journal articles, laws and regulations, and official documents relevant to the role of the School Committee. The data analysis technique used was descriptive qualitative analysis through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the School Committee contributes to educational program planning, resource provision, transparent and accountable supervision, and the strengthening of relationships between schools and the community. However, the implementation of these roles still faces several challenges, such as limited understanding among committee members, low community participation, limited resources, and ineffective communication with schools. This study concludes that strengthening the role of the School Committee can be achieved through capacity building of committee members, open communication, and active community participation